New synthesis and biological evaluation of benzothiazole derivates as antifungal agents - Herrera Cano, Natividad Carolina (2015)
In search of new antifungal agrochemicals that could replace commercially available, aryl-2-mercaptobenzothiazoles were synthesized. They were prepared by two methodologies, using both photostimulated reaction and microwave assisted reaction. These reactions took place without the use of metallic catalyst by a one-pot procedure with excellent yields (70–98%). Synthesized compounds were evaluated for fungal growth inhibition against Botrytis cinerea. Most of the compounds have an excellent antifungal activity, and three of these showed a superior inhibitory effect to commercial fungicide Triadimefon. IC50 values observed for 2-(phenylthio)benzothiazole, 2-(2-chlorophenylthio)benzothiazole, and 2-(3-chlorophenyl thio)benzothiazole were 0.75, 0.69, and 0.65 μg mL–1, respectively.